Elucidating the role of metabolic changes in modulating cell fate following treatment with anti-mitotic drugs - Wong, Alex Xing Fah (2019)
Anti-mitotic drugs are the most-commonly utilised class of chemotherapeutic agents that are administered as first-line therapy; however, their clinical success has been impeded by chemoresistance and disease relapse. Better understanding of the cellular pathways underlying this escape from antimitotic drug-induced cell death, known as mitotic slippage, is crucial for development of combinatorial therapies that can enhance existing treatment regimen in patients. Mitotic slippage describes a phenomenon where cells escape mitotic arrest and cell death following treatment with anti-mitotic drugs, and "slip" into interphase without proper chromosome segregation and cytokinesis. One of the cell fates following mitotic slippage is a cell cycle-enforced G1 arrest where cells eventually enter senescence. However, the consequences of mitotic-slippage induced senescence is unclear for anti-mitotic drug therapy. This thesis seeks to address this conundrum. In my study, my observations revealed that multinucleated post-slippage cells undergo senescence and elicit paracrine pro-tumourigenic effects, both in vitro and in vivo. The SASP factors secreted by post-slippage senescence cells promote migration, invasiveness and angiogenesis. My investigation into potential senescence effectors revealed two major metabolic pathways, autophagy and lipid metabolism, that could abrogate the tumour-promoting effects of antimitotic therapies; either by eliminating pro-tumourigenic senescent cells or by suppressing the secretion of the associated pro-tumorigenic factors. Understanding cell fate post-slippage provides opportunities for the development of novel therapeutic strategies to circumvent antimitotic drug resistance and enhance the treatment efficacy for cancer patients.